STRATEGI PEMASARAN PRODUK OLAHAN IKAN GULAMAH (Pseudocienna amovensis) DI KELURAHAN BAHARI KECAMATAN MEDAN BELAWAN (Marketing Strategy of Processed Gulamah (Pseudocienna amovensis) Products in Belawan Bahari Village Medan Belawan District) - Aulia Satria; Budi Utomo; Febrina Arli (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Belawan Bahari village is one place that provides gulamah salty fish, the fishprocessing center in North Sumatra that facilitate the gulamah processed fish seekers.Research on this marketing strategy was conducted in March-April 2016 in Belawan BahariVillage Medan Belawan District. This study aimed to determine the condition of internalfactors, external factors and the right marketing strategy to improve the gulamah fish productprocessing business. The method used is purposive sampling with the respondents thatpurposefully chosen as many as 5 gulamah fish processors and purposefully as many as 8people at parties that play a role in the marketing process. Based on the analysis of theinternal marketing environment, which utilized the main strength of the financial aspects ofthe capital itself. While the major weaknesses in the marketing of fish processed productswere the legal aspect of the business licensing and production aspects of the campaign level.Based on the analysis of the external environment of marketing, the biggest opportunity wasin the social aspect to their business processing adds as the business opportunities for localcommunities and the main threat was on the policy aspect that was the slow response of thegovernment. Based on the SWOT analysis there were four strategies that can be implementedbased on the highest rengking ie 1) SO1 : Increase the sensitivity of the processors supportedby private capital, 2) SO2: Break the lenght marketing chain becomes shorter so that increaserevenue, 3) ST1: Provide a socialization about the comparison between fish processedopportunity and fresh fish opportunity , 4) WO1: Increase the promotion by expand into avariety of media promo and various regions and use an advanced tools.Key word: Belawan Bahari Village, Gulamah Fish, Marketing Strategy, SWOT.